Purinergic inhibitory regulation of esophageal smooth muscle is mediated by P2Y receptors and ATP-dependent potassium channels in rats - Takahiko Shiina; Yuji Suzuki; Kazuhiro Horii; Tomoya Sawamura; Natsufu Yuki; Yuuki Horii; Yasutake Shimizu (Journal of Physiological Sciences)
Abstract Purines such as ATP are regulatory transmitters in motility of the gastrointestinal tract. The aims of this study were to propose functional roles of purinergic regulation of esophageal motility. An isolated segment of the rat esophagus was placed in an organ bath, and mechanical responses were recorded using a force transducer. Exogenous application of ATP (10–100 μM) evoked relaxation of the esophageal smooth muscle in a longitudinal direction under the condition of carbachol (1 μM) -induced precontraction. Pretreatment with a non-selective P2 receptor antagonist, suramin (500 μM), and a P2Y receptor antagonist, cibacron blue F3GA (200 μM), inhibited the ATP (100 μM) -induced relaxation, but a P2X receptor antagonist, pyridoxal phosphate-6-azophenyl-2,4-disulfonic acid (50 μM), did not affect it. A blocker of ATP-dependent potassium channels (KATP channels), glibenclamide (200 μM), inhibited the ATP-induced relaxation and application of an opener of KATP channels, nicorandil (50 μM), produced relaxation. The findings suggest that ATP is involved in inhibitory regulation of the longitudinal smooth muscle in the muscularis mucosae of the rat esophagus via activation of P2Y receptors and then opening of KATP channels.